National Survey of Community Policing Strategies, 1992-1993 - Annan, Sampson O. ([Verlag nicht ermittelbar], 1995)
The primary objective of this national study was to gather reliable information on the extent to which the concept of community policing had been adopted by law enforcement agencies across the country. As a program evaluation, the survey also sought to provide information on what was happening and what needed to happen within the law enforcement community with respect to the development and implementation of community policing. Following a pretest of the questionnaire, a survey package was mailed to the chief executive of each selected agency in May 1993. To minimize the number of unresolved cases and reduce the potential nonresponse bias, four follow-up contacts were made with agencies that had not responded by various stages of the data collection process. Part 1 examines the chief executive's views about community policing. Part 2 contains data on the agency's current situation, resources used, and types of police training needed in the implementation of community policing. Agencies that had implemented or planned to implement community policing identified various written policies or legislation that had been developed. Agencies that had been implementing community policing for more than one year assessed the effects of community policing. All respondents indicated programs and organizational arrangements that their agencies had in place or planned to develop, identified who in their agencies performed various community policing activities, and examined their agencies' current or planned community involvement with various activities and programs. Demographic data include the agency's sworn and civilian personnel size, number assigned to patrol and investigative divisions, size of jurisdiction served, and whether the agency provided 24-hour patrol service. The unit of analysis for the chief executive data is the individual chief executive of the agency. The unit of analysis for the agency data is the agency.